Protective Effects and Mechanism of Radix Polygalae Against Neurological Diseases as Well as Effective Substance - Jiang, Ning; Wei, Shanshan; Zhang, Yiwen; He, Wenlu; Pei, Haiyue; Huang, Hong; Wang, Qiong; Liu, Xinmin (Frontiers in Psychiatry, 2021)
Radix Polygalae (also known as Yuanzhi in China) is the dried rhizome of Polygala tenuifolia Willd. or Polygala sibirica L., which is a famous Chinese herb and has been widely used for centuries in traditional medicines including expectorants, tonics, tranquilizers, antipsychotic, and so on. This article reviews the neuroprotective effects of Radix Polygalae in preclinical models of central nervous system (CNS) disorders, especially anxiety, depression, declining cognition, Alzheimer's disease (AD), and Parkinson's disease (PD). The chemical composition of Radix Polygalae as well as the underlying mechanisms of action were also reviewed. We found that Radix Polygalae possesses a broad range of beneficial effects on the abovementioned conditions. The multifold mechanisms of action include several properties such as antioxidant and associated apoptotic effects; anti-inflammatory and associated apoptotic effects; neurogenesis, regeneration, differentiation, and neuronal plasticity improvement; hypothalamic–pituitary–adrenal axis (HPA) regulation; neurotransmitter release; and receptor activation (A2AR, NMDA-R, and GluR). Nevertheless, the detailed mechanisms underlying this array of pharmacological effects observed in vitro and in vivo still need further investigation to attain a coherent neuroprotective profile.